Technoducation and its Relevance in Enhancing Access to Higher Education in the Post Covid 19 Era in Nigeria - AMAONYE, Chinenye Blessing; ANYAEJI, Adaora; THOMPSON, Chidinma Chinenye; BABALOLA, Joel Babatunde (Journal of Education and Practice, 2022)
With the advent of Covid-19, the educational system in Nigeria was thrown into comatose as education at all levels was shutdown to curtail the spread of the virus. The closure lasted for a period of time while disrupting the academic activities across the country. Though, the Federal Government directed all tertiary institutions to switched to virtual teaching and learning as alternative form of learning for the achievement of educational programmes, the transition was slow due to the unpreparedness of Nigerian education system among other factors. To this end, this opinion paper proposes technoducation model which incorporates various technological innovations for enhancing access to higher education in Nigeria. Also, it x-rays the challenges constraining technoducation in expanding access to higher education in post Covid era.